Toward a More Just Nonprofit Sector: Leveraging a Critical Approach to Disrupt and Dismantle White Masculine Space. (3rd September 2021) - Nickels, Ashley E.; Leach, Kirk A.
Abstract : This article examines the utility of deploying a critical framework–grounded in critical race theory (CRT), feminist theory, and intersectionality–in nonprofit and voluntary studies. We argue that these theoretical perspectives, which emphasize lived experience and sense-making, while simultaneously situating these experiences within broader socio-political and historical contexts, offer a useful analytic lens for centering the narratives and experiences of marginalized or muted voices, which serve to disrupt and dismantle the hegemony of Whiteness and masculinity in nonprofit spaces.